2010
DOI: 10.1021/ja104766z
|View full text |Cite
|
Sign up to set email alerts
|

Fast Water Oxidation Using Iron

Abstract: Photolysis of water, a long-studied strategy for storing solar energy, involves two half-reactions: the reduction of protons to dihydrogen and the oxidation of water to dioxygen. Proton reduction is well-understood, with catalysts achieving quantum yields of 34% when driven by visible light. Water oxidation, on the other hand, is much less advanced, typically involving expensive metal centers and rarely working in conjunction with a photochemically powered system. Before further progress can be made in the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
432
3
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 598 publications
(448 citation statements)
references
References 19 publications
9
432
3
4
Order By: Relevance
“…1 top and an I2M mechanism is found when the favored species resemble those of the oxyl radical form depicted in the lower part of Figure 1 Recently several first row transition metal complexes have been reported as catalysts for the water oxidation reaction. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] While these catalysts are of interest because of their high abundance and low toxicity, their performance is much poorer than their Ru or Ir analogues, and in addition their mechanistic pathways are in most cases basically unknown. [28][29][30][41][42][43] We have very recently reported a new complex based on Cu, containing the amidate ligand OPBAN that can carry out the water oxidation reaction in a very efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…1 top and an I2M mechanism is found when the favored species resemble those of the oxyl radical form depicted in the lower part of Figure 1 Recently several first row transition metal complexes have been reported as catalysts for the water oxidation reaction. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] While these catalysts are of interest because of their high abundance and low toxicity, their performance is much poorer than their Ru or Ir analogues, and in addition their mechanistic pathways are in most cases basically unknown. [28][29][30][41][42][43] We have very recently reported a new complex based on Cu, containing the amidate ligand OPBAN that can carry out the water oxidation reaction in a very efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…Citing just a small portion of the broad interest in molecular water oxidation: ruthenium dimers [9][10][11][12] and tetramers, [13][14][15] cobalt tetramers, 16,17 manganese dimers 18 along with recent work detailing single-site catalysts [19][20][21][22][23][24][25][26] all illustrate the diversity of successful catalysts. More recently, a variety of Cp*Ir complexes (Cp* = C 5 Me 5 -) have been shown to act as efficient water oxidation precatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Tiago de Oliveira et al 32 reported the synthesis of an oxoiron(V) ( An Fe V (O)(OH) species has been implicated as the active oxidant responsible for the cis-dihydroxylation of C = C double bonds 2,4,33 and the oxidation of water 34 in a number of ironcontaining non-haem natural and model systems, but with only indirect proof of its existence [35][36][37] . However, the spectroscopically characterized [(TAML)Fe V (O)] − anion, which is the only known isolable oxoiron(V) species in the literature, was found to be a sluggish oxidant 32 38 . Therefore, the involvement of Fe V (O)(OH) intermediates in oxygenation reactions remained doubtful until very recently 39 .…”
mentioning
confidence: 99%